Clinical risk factors for moderate and severe antituberculosis drug-induced liver injury - Liu, Quanxian; Huang, Lu; Yan, Hong; Zong, Zhaojing; Chen, Zhenyong; Wu, Xiaoyan; Chen, Ling; Lan, Yuanbo (Frontiers in Pharmacology, 2024)
Objective: To analyze the clinical and laboratory characteristics and to identify predictors of moderate to severe anti-tuberculosis drug-induced liver injury (ATB-DILI) in patients with tuberculosis. Methods: This prospective study enrolled TB patients treated with first-line antituberculosis drugs at the Affiliated Hospital of Zunyi Medical University between May 2022 and June 2023. The occurrence of ATB-DILI was monitored, and demographic and clinical data were gathered. We analyzed risk factors for the development of moderate to severe ATB-DILI. Results: ATB-DILI was detected in 120 (10.7%) of the patients, with moderate to severe ATB-DILI occurring in 23 (2.0%) of the 1124 patients treated with anti-tuberculosis treatment. Multivariate cox regression analysis identified malnutrition (HR = 4.564, 95%CI: 1.029-20.251, P=0.046) and hemoglobin levels < 120g/L (HR = 2.825, 95%CI: 1.268-11.540, P=0.017) as independent risk factors for moderate to severe ATB-DILI. Conclusion: The incidence of moderate to severe ATB-DILI was found to be 2.0%. Malnutrition and hemoglobin levels below 120g/L emerged as significant independent risk factors for the occurrence of moderate to severe ATB-DILI in this patient population.